2007
DOI: 10.1016/j.etap.2006.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mandrax and Cannabis on the cellular function of chick embryonic neurons

Abstract: Cannabis and Mandrax abuse is unique to South Africa; and most research has focused on the socio-economic impact rather than the adverse effects on the developing brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…[19][20][21][22][23][24][25] It is well documented that cannabis and Mandrax abuse in combination is unique to South Africa, the abuse of these drugs mainly occurs in the form of inhalation by smoking although it can be swallowed or injected. 26 Within a few minutes of smoking Mandrax, the user usually feels relaxed, calm and peaceful although some may feel aggressive as the effects of the drug start wearing off. 27,28 The effects last for several hours during which the user will have a dry mouth and very little appetite.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25] It is well documented that cannabis and Mandrax abuse in combination is unique to South Africa, the abuse of these drugs mainly occurs in the form of inhalation by smoking although it can be swallowed or injected. 26 Within a few minutes of smoking Mandrax, the user usually feels relaxed, calm and peaceful although some may feel aggressive as the effects of the drug start wearing off. 27,28 The effects last for several hours during which the user will have a dry mouth and very little appetite.…”
Section: Original Articlementioning
confidence: 99%
“…Depression, insomnia, anxiety and irritability, headaches, restlessness and eating problems are also common among users. [26][27][28][29] One study investigating the prevalence of recent drug use among 1050 individuals arrested by the police in South Africa revealed that 45% tested positive for at least one drug (mainly cannabis or Mandrax). 31 Significantly, none of the studies accounted for in the literature investigated Mandrax use among prison inmates or the possibility of it being a contributing factor to STI risk practices among this population.…”
Section: Original Articlementioning
confidence: 99%